PENGHITUNGAN DAN PENENTUAN KERUGIAN KEUANGAN NEGARA HUBUNGANNYA DENGAN HUKUMAN PIDANA DALAM PUTUSAN PENGADILAN TINDAK PIDANA KORUPSI DI INDONESIA (Tinjauan terhadap 109 Putusan Pengadilan Perkara Tindak Pidana Korupsi Tahun 2010 - 2011 di Wilayah Pengad - HERNOLD F. MAKAWIMBANG, Jurnal Mahasiswa S2 (Jurnal NESTOR Magister Hukum, 2012)
AbstractOf Corruption in Indonesia more massive spread in the community and legal uncertainty in the handling of corruption cases occur due to unclear defisini state assets, this implies also which agency has the right and authority to declare the state a loss has occurred. In fact, the formulation of the country's loss, used as an element in corruption cases to be proven at trial. In connection with the development of the judge's decision to confiscate the money, goods or assets results